Alone Together: Computer-Mediated Communication in Leisure Time During and After the COVID-19 Pandemic - Meier, Jennifer V.; Noel, Josephine A.; Kaspar, Kai (Frontiers in Psychology, 2021)
In spring 2020, the COVID-19 outbreak was declared a global pandemic and several lockdowns followed in Germany. To weaken the spread of the virus SARS-CoV-2, people were required to reduce their face-to-face contacts with others. Computer-mediated communication offers opportunities to stay in touch with important people and still meet social needs. During the first lockdown in spring 2020, we collected data from 679 participants to explore the role of computer-mediated communication for social interaction in the context of leisure activities and how personal characteristics contribute to such media use. Results showed that people complied with the restriction and shifted their communication to several media, above all instant messengers and video calls. Many leisure activities were performed via computer-mediated communication, especially low-key activities, such as just talking or simply spending time together. Perceived social closeness to others was positively related to quality and quantity of computer-mediated communication. The extent of leisure activities that people experienced with others via communication media was higher among younger individuals, males, and individuals with higher scores on positive state affect, extraversion, openness, and fear of missing out. The preference for solitude showed a negative relation. The motivation to continue using media for communication after the pandemic was strongly related to quality and quantity of actual use. Low extraversion and high openness were related to higher motivation for future use. Implications such as the importance of providing fast internet and good usability of communication media as well as the relevance of increasing people’s media literacy are discussed.